Annual Report of RADARC - 2001 - Gao, Yongqi; Drange, Helge; Bentsen, mats; Johannessen, Ola M.; Petersson, Lasse H. (Zenodo, 2002)
An existing 3-D coupled ocean and sea ice model is used to include the transport and dispersal of radionuclides. The coupled ocean-sea ice-radionuclides model is validated against the observed pathway and distributions of the radionuclides. The specic tasks are as follows: Subtask 1. Modifications, testing and validation of an existing tracer advection and dispersal module online coupled to the North Atlantic-Arctic mo del, Subtask 2. Coding and testing of a module describing the input of various terrestrial and atmospheric sources of radionuclides, Subtask 3. Indentification and interpolation of data sets for validation of simulated radionuclides transport and dispersal, Subtask 4. Validation of the simulated radionuclides transport and dispersal fields. NERSC Technical report no. 210. Funded by the European Union under Contract no. ICA2-CT-2000-10037